2016
DOI: 10.1247/csf.16014
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Extracellular Vesicles: Pathobiological Roles in Disease

Abstract: ABSTRACT. Over the past decade, many studies have been conducted on extracellular vesicles (EVs) in the fields of basic and clinical research. EVs are small sized membranous vesicles generated from many type of cells upon activation by environmental stresses such as heat, hypoxia, and irradiation. EVs theoretically consist of microparticles/microvesicles, exosomes, and apoptotic bodies by different productive mechanisms. Clinically, EVs are observed in the blood stream of patients suffering from acute and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 64 publications
0
44
0
Order By: Relevance
“…Whether EVs can accelerate disease progression or induce vascular protection is still a matter of debate. Numerous evidence has shown that EVs can play a major role in inflammation, thrombosis and coagulation‐all of which are conditions that are involved in atherogenesis . However, recent data challenged the presumed deleterious role of EVs and suggested that EVs promote cell survival, exert anti‐inflammatory effects, counteract coagulation processes or induce endothelial regeneration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether EVs can accelerate disease progression or induce vascular protection is still a matter of debate. Numerous evidence has shown that EVs can play a major role in inflammation, thrombosis and coagulation‐all of which are conditions that are involved in atherogenesis . However, recent data challenged the presumed deleterious role of EVs and suggested that EVs promote cell survival, exert anti‐inflammatory effects, counteract coagulation processes or induce endothelial regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous evidence has shown that EVs can play a major role in inflammation, thrombosis and coagulation-all of which are conditions that are involved in atherogenesis. [13][14][15][16] However, recent data challenged the presumed deleterious role of EVs and suggested that EVs promote cell survival, exert anti-inflammatory effects, counteract coagulation processes or induce endothelial regeneration. 17,18 Taken together, the role of EVs in the maintenance of vascular homeostasis is more complex than initially considered.…”
Section: Introductionmentioning
confidence: 99%
“…; Cocucci & Meldolesi, ; Shintaku & Maeno, ; Yamamoto et al. ). Molecular mechanisms involved in the release of these vesicles as well as conditions influencing the occurrence of blebbing (Tokuda et al.…”
Section: Discussionmentioning
confidence: 99%
“…Internucleosomal fragmentation of chromatin is performed by speciic apoptotic nucleases during early phase of the process [45]. Nuclear antigens, including nucleosomes, moved then to litle bulbs of cell membrane, so-called apoptotic bodies [46]. Interestingly, in some virus infections, endogenous nucleoproteins are bundled together with virions and, thereby, can be jointly presented in apoptotic bodies [47].…”
Section: Normal Generation and Clearance Of Extracellular Dnamentioning
confidence: 99%